Research of the Method of Selection of Modification Coefficient Value of the Planetary Involute Gear with Small Teeth Difference based on Matlab - Feng Ding; Yang Hang; Feng Yijing; Wang Jie; Xiang Zhengxin; Wu Han (Jixie chuandong)
According to the definition of planetary gear transmission with small teeth difference,the selection of value of modification coefficient is the key in the design of planetary gear reducer with small teeth difference. By analyzing and comparing common modification coefficient selection method,based on the constraints theory of the displacement gear modification coefficient selection and using Matlab software assisted calculation,a small teeth difference planetary involute gear modification coefficient value selection method is presented.Through the examples of validation,the external gear modification coefficient calculated by Matlab programming is smaller than calculated by conventional design,but has a large degree of the contact ratio,the results show the feasibility of Matlab programming is higher.